Mini-review on the novel synthesis and potential applications of carbazole and its derivatives - Xu, Zhichao (2024)
Microporous organic polymers (MOPs) are a new type of porous materials, which have advantages of synthetic diversity, chemical and physical stability, microporous size controllability, etc. MOPs indicate broad applications in various fields such as heterogeneous catalysis, gas adsorption, separation, and storage. In recent years, MOPs have attracted an enormous attention in greenhouse gas capture due to their great potential in physisorptive gas storage. Carbazole and its derivatives have been studied extensively as Metal-Organic Polyhedra (MOPs) building blocks due to their unique structural features and versatile functionalization possibilities. This paper systematically reviews the synthesis, characterization and application of carbazole-based polymers, and relationship of structures and properties of these polymers. The application of the polymers in carbon dioxide (CO2) capture field is analysed taking advantage of their adjustable microporous structure and electron rich properties. This review also provides novel insights regarding functional polymer materials that have high ability of greenhouse gas capture and absorbing selectivity will be obtained by reasonable molecular design and efficient synthesis.